2018
DOI: 10.1037/edu0000215
|View full text |Cite
|
Sign up to set email alerts
|

An information distortion model of social class differences in math self-concept, intrinsic value, and utility value.

Abstract: In this paper we develop an information distortion model (IDM) of social class differences in self-beliefs and values. The IDM combines psychological biases on frame-of-reference effects with sociological foci on ability stratification. This combination is hypothesized to lead to working class children having more positive math self-beliefs and values than equally able salariat children. We further suggest that the same conditions that give rise to the working class benefit in self-beliefs and values are assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 75 publications
(125 reference statements)
2
27
0
Order By: Relevance
“…This fact, also, is consistent with prior studies, including the works of Susperreguy, Davis-Kean, Duckworth and Chen (2018) [17] and Weidinger, Steinmayr and Spinath (2019) [98]. According to several authors, differences in self-concept may be found across educational levels, that is, between primary, secondary, and postsecondary education, but are more difficult to find within the same educational level [14,15].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This fact, also, is consistent with prior studies, including the works of Susperreguy, Davis-Kean, Duckworth and Chen (2018) [17] and Weidinger, Steinmayr and Spinath (2019) [98]. According to several authors, differences in self-concept may be found across educational levels, that is, between primary, secondary, and postsecondary education, but are more difficult to find within the same educational level [14,15].…”
Section: Discussionsupporting
confidence: 90%
“…Marsh et al (2019) [14] defined self-concept as individuals' self-perceptions formed through their own experiences and interpretations of their environment. According to Parker, Marsh, Guo, Anders, Shure, and Dicke (2018) [15], an alternative definition is the sum total of individuals' mental and physical characteristics and their own evaluation of them. Hence, self-concept is believed to have a complex structure with different factors comprising it.…”
Section: Self-conceptmentioning
confidence: 99%
“…When considered from a within-country perspective, traditional dividing lines between educational systems evaporated. Nordic countries have often been shown to be among the most equal in between-country studies (e.g., Parker et al, 2016Parker et al, , 2017. When considering within-country estimates however, Iceland and Sweden had some of the most evident declines in achievement and increases in inequality of all countries considered.…”
Section: Discussionmentioning
confidence: 99%
“…Widespread and systematic inefficiencies in child assignment could account for the results noted here (see Pfeffer, 2015). Indeed, PISA data suggest that misplacement occurs across the socioeconomic ladder (Parker et al, 2017). For example, Maaz, Trautwein, Lüdtke, and Baumert (2008) note that in the Germanic system, parents from well-off families often ensure that their children are located in university track systems even when teacher recommendations are for lower track placements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation